Abrogation of prostaglandin E-EP4 signaling in osteoblasts prevents the bone destruction induced by human prostate cancer metastases - Watanabe, K; Tominari, T; Hirata, M; Matsumoto, C; Maruyama, T; Murphy, G; Nagase, H; Miyaura, C; Inada, M (Elsevier, 2016)
The metastasis of tumors to bone is known to be promoted by prostaglandin E2 (PGE2) produced by the tumor host stromal tissue. Although bone metastases frequently occur in prostate cancer patients, the significance of PGE2 in stromal responses to the tumor is not known. In this study, we report that PGE2 and its receptor EP4 play a pivotal role in bone destruction and metastasis in an experimental metastasis model of prostate cancer in nude mice. Using human prostate cancer PC-3 cells that are stably transfected with luciferase, we showed that the development of bone metastasis was accompanied by increased osteoclastic bone resorption in the bone metastasis microenvironment, and could be abrogated by an EP4 receptor antagonist. The growth of PC-3 cells in vitro was not influenced by PGE2 or by the EP4 receptor. However, cell-cell interactions between fixed PC-3 cells and host osteoblasts induced PGE2 production and RANKL expression in the osteoblasts. Addition of an EP4 antagonist suppressed both PGE2 and RANKL expression induced by the PC3-osteoblast interaction, which would have consequent effects on osteoclast activation and osteolysis. These results indicate that the blockage of PGE2-EP4 signaling prevents the bone destruction required for prostate cancer metastases, and that this is, in part due to the abrogation of bone cell responses. The study provides further evidence that an EP4 antagonist is a candidate for the treatment of prostate cancer in the blockade of bone metastasis.